2022
DOI: 10.1080/09571736.2022.2110607
|View full text |Cite
|
Sign up to set email alerts
|

Levels of foreign language enjoyment, anxiety and boredom in emergency remote teaching and in in-person classes

Abstract: The present mixed-method study focuses on levels of foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA) and foreign language boredom (FLB) among 168 Arab and Kurdish English as a foreign language (EFL) learners in both in-person and emergency remote teaching (ERT) classes. Statistical analyses revealed that learners experienced significantly more FLE, more FLCA, and less FLB in in-person classes than in ERT classes. The qualitative data revealed a more nuanced picture about the things l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
3
10
1
Order By: Relevance
“…The online education promoted by the pandemic has put much pressure on students and teachers both, and has somehow threatened their cognitive and affective well-being (Casañ-Núñez, 2021; Shahnama et al, 2021b;Dewaele et al, 2022a). Regarding the construction of a positive climate of foreign or second language learning, and given the interplay of cognition and emotion, underlying the positive psychology movement of SLA, teachers should be encouraged to employ different strategies to create a positive climate in online classes to develop positive emotions and effective interactions in which learning is mixed with pleasure (Casañ-Núñez, 2021).…”
Section: Online Classroom Climatementioning
confidence: 99%
See 2 more Smart Citations
“…The online education promoted by the pandemic has put much pressure on students and teachers both, and has somehow threatened their cognitive and affective well-being (Casañ-Núñez, 2021; Shahnama et al, 2021b;Dewaele et al, 2022a). Regarding the construction of a positive climate of foreign or second language learning, and given the interplay of cognition and emotion, underlying the positive psychology movement of SLA, teachers should be encouraged to employ different strategies to create a positive climate in online classes to develop positive emotions and effective interactions in which learning is mixed with pleasure (Casañ-Núñez, 2021).…”
Section: Online Classroom Climatementioning
confidence: 99%
“…In recent years, marked by a rapidly growing use of online L2 learning, the prevalent use of mobile and portable devices as well as the use of wireless technology for language learning have instigated more interest in using these technologies in online language learning programs too (Kohnke and Moorhouse, 2022). Due to the unique setting of online language classes, language learners might experience different positive and negative emotions in this setting (Dewaele et al, 2022a). Therefore, given the recent positive psychology movement in the field of SLA, turning this setting into a positive climate can take place via a reflection and adoption of the main techniques and strategies introduced in the literature of positive climate and social interactions.…”
Section: Implications Of Positive Classroom Climate For Online L2 Cla...mentioning
confidence: 99%
See 1 more Smart Citation
“…As for the online language learning context, Derakhshan et al ( 2021 ) uncovered teachers' long, tedious monologs, students' insufficient participation, carelessly-chosen tasks and technical problems as the main sources of boredom, while Yazdanmehr et al ( 2021 ) revealed user-unfriendly requirements of online education, such as physical distance or sedentary position, are antecedents of boredom likewise. Moreover, Dewaele et al ( 2022 ) found that the lack of live personal interactions and the monotonous teacher delivery could induce students' disengagement and cause boredom.…”
Section: Introductionmentioning
confidence: 99%
“…Chengchen Li et al (2023) and Li (2022) showed that this negative, low-arousal emotion also exerts a powerful influence on learner FL performance as it can cause disengagement. The logical next step was to investigate how the three emotions—FLE, FLCA and FLB—were connected and how they jointly affected performance and achievement (Dewaele, Albakistani, et al, 2022; Dewaele, Botes, et al, 2022; Li, 2022; Li & Han, 2022; Li & Wei, 2022). These studies answered calls for increased diversity in the range of emotions, in methodological approaches, in the use of sophisticated statistical methods, and in language learning populations (Dewaele & Li, 2020; In'nami et al, 2022; MacIntyre et al, 2019).…”
mentioning
confidence: 99%